Teknik Marketing Produk pada UKM Suka Nicky Banjarnegara - Krisnhoe Rachmi Fitrijati; Atiek Sri Purwati; Pemata Ulfah; Umi Pratiwi (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
Innovation cannot be separated from business life because innovation is the spirit or soul of a company to develop. Therefore, innovation management is an important factor in determining the development of small and medium enterprises (SMEs). The role of SMEs in a country's economy is very important. SMEs symbolize the strength of a country's economic development. UKM Suka Nicky is one of the UKMs that has been established since 1996, starting from a small tempe chips business carried out by Sukini as a business actor. Some of the challenges that have been experienced in developing the UKM Suka NIcky business include product innovation, advances in Information Technology, product variations and market segmentation. The aims and objectives of implementing community service activities at UKM Suka Nicky are one form of implementing the tri dharma of higher education which must be carried out by lecturers as a form of community service. This program is expected to increase insight into marketing strategies, which in turn can provide additional knowledge, knowledge that can be used as additional income so that prosperity can be achieved.